Technology Acceptance Model: Is It Trends in The Sustainability of SMEs? - Margo Purnomo; Erna Maulina; Aulia Rizki Wicaksono; Muhamad Rizal (Budapest International Research and Critics University, 2022)
The purpose of this research is to do a literature review related to the topic of Technology Acceptance Model on any SMEs. This research is a qualitative method using a systematic literature review method. The search was carried out on the Scopus electronic data base in the 2004-2019 publication years which was published in the form of a scientific journal with certain criteria. Based on the results of the study, it is known that the results of the publication of the Technology Acceptance Model began to increase significantly in 2014, and continued to increase until 2019 and were mostly carried out in America and Indonesia. Regarding the locus of research, the researcher concludes that research on Technology Acceptance Models in SMEs has been widely studied in Manufacturing SMEs. This type of research in the form of quantitative descriptive is the type of research that is most often used. However, the type or type of paper with the type of Validation Research using quantitative or qualitative methods can be used for further research. The results of this systematic literature review can provide an overview of opportunities to explore new topics in the Technology Acceptance Model for SMEs or exploit existing topics.